2018
DOI: 10.1371/journal.pone.0199573
|View full text |Cite
|
Sign up to set email alerts
|

A G542X cystic fibrosis mouse model for examining nonsense mutation directed therapies

Abstract: Nonsense mutations are present in 10% of patients with CF, produce a premature termination codon in CFTR mRNA causing early termination of translation, and lead to lack of CFTR function. There are no currently available animal models which contain a nonsense mutation in the endogenous Cftr locus that can be utilized to test nonsense mutation therapies. In this study, we create a CF mouse model carrying the G542X nonsense mutation in Cftr using CRISPR/Cas9 gene editing. The G542X mouse model has reduced Cftr mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 67 publications
(82 reference statements)
2
45
0
Order By: Relevance
“…Affinity-purified polyclonal antibodies were raised against recombinant peptides of mouse SGLT1 (NP_062784.3; amino acid residues 576-610) and of mouse CFTR (NP_066388.1; 634-675 and 1438-1476), respectively, using the same method as described previously. 21 Specificity of each antibody was confirmed by immunostaining in Sglt1-knockout (a gift from Dr. Koepsell) 22 or Cftr null (G542X mutation generated in Case Western CF Mouse Model Core) 23 mouse tissues ( Supplementary Figures 1 and 2).…”
Section: Antibody Productionmentioning
confidence: 99%
“…Affinity-purified polyclonal antibodies were raised against recombinant peptides of mouse SGLT1 (NP_062784.3; amino acid residues 576-610) and of mouse CFTR (NP_066388.1; 634-675 and 1438-1476), respectively, using the same method as described previously. 21 Specificity of each antibody was confirmed by immunostaining in Sglt1-knockout (a gift from Dr. Koepsell) 22 or Cftr null (G542X mutation generated in Case Western CF Mouse Model Core) 23 mouse tissues ( Supplementary Figures 1 and 2).…”
Section: Antibody Productionmentioning
confidence: 99%
“…The CFTR gene is expressed in abundance throughout the intestine (17). Mouse models of CF have demonstrated that CFTR dysfunction leads to mucus accumulation within the intestinal lumen, disturbed motility, small bowel bacterial overgrowth, and inflammation with an abnormal innate immune response (18).…”
Section: Discussionmentioning
confidence: 99%
“…A mouse carrying the G542X nonsense mutation in the CFTR locus was generated by CRISPR nucleases showing common manifestations of CF determined by the absence of CFTR ion channel, such as intestinal obstruction and reduced growth [98].…”
Section: Genome Editing For the Development Of Cf Modelsmentioning
confidence: 99%